(untitled) (Archives of Criminology, 1960)
The Polish criminal law treats everybody who has completed his or her seventeenth year as an , adult" and does not provide for any separate principles of responsibility, nor for the possibility of applying any special means with regard to young adults, i.e. persons in the transition age between minority and full adult age. The Department of Criminology of the Institute of Legal sciences has, in the course of its investigation concerning the delinquency of juveniles (up to 17 years of age) and of young adults, singled out offenders between the seventeenth and the twentieth year of age, and carried out research on the problem of the forms which their delinquency assumed in the light of judicial statistics. During the period under investigation the total number of persons age 17 to 20 among the whole population of Poland amounted to an approximate figure of between 1 800 000 and 1 900 000 persons, including from 910 000 to 960 000 men and from 900 000 to 960 000 women (the total of Poland’s population aged over 17 amounted to from 16 600 000 to 19 000 000 people, of whom between 7 700 000 and 9 200 000 were men, and between 8 900 000 and 9 800 000 – women). The materials of judicial statistics on the basis of which our calculations have been compiled proceed from the summing up of the records entered on special cards made by the law-courts in the event of their having convicted an accused person, and with regard to every person convicted by the law-court in question for a felony or a misdemeanor , i.e. for acts provided for in the 1932 Criminal Code, still in force, or else in special criminal statutes, and for which the penalty is one of more than three months custody or a fine of more than 4500 zlotys. The above-mentioned cards, after the use has been made of them for statistical purposes, are preserved in the record of convicts in order to make possible the establishment of any previous delinquency of an apprehended offender. Because of the law-courts frequent failing to send such cards to the Register of Convicts, recourse has been had to another source of information concerning convictions, namely judicial reports’ which have yielded data making it possible to go in for an approximate estimation of the actual number of all the persons convicted by the law-courts, and being over the age of 17. The diminution of the number of persons convicted in 1953 as compared with 1952 is a result of the carrying out of the Amnesty Act of the end of 1952, while that of 1957 as compared with 1955 seems to be connected to a considerable extent, with the very serious increase, within the year 1957, of the number of criminal cases awaiting to be tried by the courts. During the 1951 to 1957 period the rate of convictions pronounced against adults increased by 19 per cent, while the corresponding figure for young adults was 26 per cent. The delinquency coefficients quoted above show that in 1951 one out of each 64 young adult inhabitants of Poland was convicted by the law-courts, while in 1957 it was one out of every 57. If we take into consideration all the convicted persons adults and juveniles together, it will appear that in the years 1951 to 1957 persons aged under 17 years (juveniles) constituted between 9 and 16 per cent of the total of persons convicted by the courts; persons aged under 21 (juveniles and. young adults together) - from 21 to 27 per cent; persons under 25 years of age - from 34 to 40 per cent, and persons under 30 years of age - between 53 and 57 per cent. The convicted persons aged 17 to 29 formed a group comprising from 46 to 48 per cent of the total of convicted persons in every single year of the 1951 to 1957 period, so that the age of nearly one in every two convicted persons was comprised within the limits of from 17 to 29 years. The researched number of delinquency coefficients provide us with an appropriate knowledge of the rate of convictions of young adults as compared with further age groups of convicted adults, as well as of the differences in the rate of convictions of men and women. Thus the rate of convictions in the pre-war period (1937) was considerably higher than in the years 1951 to 1957. Particularly big differences, yielding coefficients nearly twice as high, can be noticed with regard to men aged 17 to 20, 21 to 24 and 25 to 29. On the other hand, the rate of convictions of women in 1937 very closely approximated the present-day rate. In the years 1951 to 1957 the amount of young adults delinquency coefficients for men towered high above the coefficients for the remaining age groups (the only exception can be recorded in 1957, with regard to the 25 to 29 years age group). It ought, however, to be emphasized that the coefficients for the 21 to 24 years age group for men are somewhat lower than they ought to be, since they have been calculated for all men within the above age limit while in a reality number of them who were then doing military service would be tried by courts-martial, the sentences of which have not been taken into consideration in the present contribution. Among women (similarly as in 1937) the highest rate of convictions was that for women aged 21 to 24, while the coefficients for young adults were lower than those for the 30 to 39 of age group. The mutual relation between the number of convicted men and women has undergone a considerable change as compared with the pre-war period; this change was most clearly marked in the initial years of the 1951 to 1957 period; it consisted in a diminution of the difference between the number of men and women convicted. In the years 1951 to 1957 the highest rate of convictions of young adult offenders (incidentally the same was true of juveniles as well) was shown by the two largest cities, Warsaw and Łódź, the voivodeships of the Western Territories and the most urbanized and industrialized area in the whole of the country - the voivodeship of Katowice. The information quoted so far was based on the estimative evaluation of the actual number of persons convicted, which we have mentioned above. Since an analogous estimation of the data concerning the kinds of offences committed by the persons convicted in the years 1951 to 1957 seemed too risky, in discussing the information concerning them we have relied directly upon the calculations furnished in the conviction cards made by the law-courts. Young adults delinquency seems to be considerably less differentiated than that of adults: first and foremost, offences property, and then against life and health, constitute those acts for which nearly three out of every four young adults punished by the courts in the years 1951 to 1957 were convicted. Apart from these two categories, it was only the offences against documents, in practice consisting mostly in remaking or forging various kinds of certificates and others documents, that young adults were more numerously represented than adults as a total. The percentage of persons convicted for offences against property among the several age groups of convicts clearly diminished as we passed from the younger to the older age groups. Among the older group of juveniles they still constituted 83 per cent, while among young adults – a mere 50.9 per cent. In the case of convictions for offences against life and health the opposite was true, while such offenders were most numerous among young adults (as much as 22.5 per cent of all the persons convicted in this group), while among the groups of adults nearest in age they were already somewhat less numerous. Speaking of the most important differences in the structure of the delinquency of young adults men and women, it may be worth while to note the fact that among women aged 17 to 20 there were relatively fewer convictions for offences against social property that among men of the same groups, and rather more convictions for offences against individual property; similarly, there were several times less convictions among women of the same age for offences against life and health, authorities and offices, as well as against morals, while women were several times more frequently convicted for offences against documents. The most important changes in the structure of young adults delinquency in the course of the 1951 to 1957 period were: a diminution of the share of those convicted for offences against property (60.4 per cent in 1951 and 58.3 per cent in 1952 – as against 52.2 per cent in 1955 and 50.9 per cent in 1957), and a very considerable increase of the percentage of young adults convicted for offences against life and health (from 11.8 per cent in 1951 and 15.1 per cent in 1952 - to 20.2 per cent in 1955 and 22.5 per cent in 1957). The latter change is attributed, first and foremost, to an increase in the activities of the police in pursuing such offences. Among the young adults convicted for offences against property (whether social or individual) the tremendous majority consisted of persons convicted for theft (92 per cent and 74 per cent respectively). In 1957 394 young adults were convicted for robbery (out of a total of 1004 persons convicted for the same offence). On the other hand, among the persons convicted for such offences as the receiving of stolen goods (a total of 5457 persons in 1957) there were relatively very few young adults (522 persons), similarly as in the case of convictions for fraud (119 young adults as against 1225 adult persons convicted in 1957). About 28 per cent of all the young adults convicted in 1957 for offences against life and health were prosecuted for infringement of bodily inviolability (1620 persons), 28 per cent for inflicting slight bodily harm (1655 persons). Nearly one out of every three young adults (31 per cent, 1857 persons) convicted for offences against life and health in 1957 was convicted for participation in a brawl (if he used a dangerous tool or else if the result was death or grievous injury to the body). Within the same year 38 young adults were convicted of murder and manslaughter, out of a total number of 263 adults, 10 young adults of infanticide, out of a total number of 31 adults, and 51 young adults of unintentionally causing death, out of a total number of 333 adults. Out of a total of 134 young adults convicted for sexual offences in 1957 there were 55 who had committed immoral acts with juveniles under 15 years of age, 64 were convicted for rape, 1 for incest, 8 for various forms of abetting to prostitution and deriving profits from it, and 6 for various other offences included in this group.